Analisis Perbandingan Variasi Dimensi Fondasi Tiang Pancang Pada Jembatan Sambirejo di Tol Solo-Kertosono - Wulandari, Malinda; Solin, Dian Purnamawati; Farichah, Himatul (AGREGAT, 2023)
The foundation is one of the essential elements in a construction. Therefore, during the process of designing, meticulous design becomes important. This involves a careful consideration of soil investigation and upper structure data. Apart from these two aspects, the selection of the appropriate foundation type, dimensions, and depth are also crucial factors to consider during process of designing. Hence, in this research the analysis of the bearing capacity of pile foundations is conducted with variations in dimensions of 500, 600, and 800 to obtain effective and suitable dimensions for the case study area of the Solo-Kertosono toll road. Additionally, this study includes an analysis of the efficiency of pile by calculating the bearing capacity, settlement and the cost and time estimation plan. In summary, the result of this research indicate that the most effective and suitable dimension is a foundation with a diameter of 800 mm.